2017
DOI: 10.1007/s10620-017-4738-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of 1,25-Dihydroxy Vitamin D3 on Pepsin–Trypsin-Resistant Gliadin-Induced Tight Junction Injuries

Abstract: VD3 has protective effects against PT-G-induced TJ injuries both in vitro and in vivo, which may correlate with the disturbance of the MyD88-dependent zonulin release signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Increases of intraepithelial lymphocytes and epithelial cell proliferations with crypt hyperplasia, as well as reduced enterocyte differentiation, characterize pathological lesions. In addition, CD4+ cells participate to the activation of B cells throughout Th2, resulting in the production of antibodies to gluten and transglutaminase [18,[38][39][40][41].…”
Section: Vitamin D and Immune Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Increases of intraepithelial lymphocytes and epithelial cell proliferations with crypt hyperplasia, as well as reduced enterocyte differentiation, characterize pathological lesions. In addition, CD4+ cells participate to the activation of B cells throughout Th2, resulting in the production of antibodies to gluten and transglutaminase [18,[38][39][40][41].…”
Section: Vitamin D and Immune Systemmentioning
confidence: 99%
“…Although the main external trigger is gluten, which is able to activate both innate and adaptive immune systems, the intestinal barrier plays a key role. Indeed, in susceptible individuals, an early disruption of the gut barrier will result in an increased permeability that could precede the onset of immune events induced by gluten [18,38].…”
Section: Vitamin D and Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…In this issue of Digestive Disease and Sciences, Dong et al published an innovative paper that demonstrated the beneficial effects of the vitamin D metabolite 1,25-dihydroxycholecalciferol (VD3) or calcitriol, a health-promoting molecule [9]. VD3 is thought to be the most active metabolite of vitamin D in humans, a modulator of calcium homeostasis and regulator of electrolytes and blood pressure.…”
mentioning
confidence: 99%